Aid effective public-private partnerships for reproductive health - Hutchison, Deborah Rubbens
This study aimed to develop guidelines on how to develop and implement public-private partnerships in such a way that they are most likely to contribute to aid effectiveness. The effectiveness of aid has been questioned from the start. After over half a century of aid, the health status in developing countries is stagnant at best. Aid effectiveness debates have resulted in numerous declarations and calls for action. The latest development is the emphasis on the need for governmental aid organizations to partner with the private sector to not only leverage resources but also skills and share knowledge. Private sector involvement in aid has grown significantly in recent years and the value of their contributions has not gone by unnoticed. Public-private partnerships are thus considered the new way forward for aid delivery. Questions, however, remain on whether they truly contribute to aid effectiveness and how they can best be set up to ensure greatest likelihood of aid effectiveness. To answer these questions, we reviewed numerous publicly available as well as internal document, conducted interviews with forty-seven senior-level individuals at various public and private aid organizations and analyzed twenty-eight public-private partnerships for reproductive health in two countries: Kenya and the Philippines. The analysis followed a multi-tiered approach. First, a set of five aid effectiveness principles that are practical, realistic and agreeable for public and private aid organizations alike was established. Next, to gain a full understanding of how public-private partnerships are developed and implemented, twenty-eight public-private partnerships for reproductive health were studied and patterns were identified. While no one-size-fits-all-model currently exists and partnerships are generally developed ad hoc, some clear pathways for public-private partnerships were established that cover their full life cycle. Further, based on interviewee feedback a set of five viability principles for public-private partnerships was identified and analyzed in the light of the earlier established aid effectiveness principles. This allowed us to determine when public-private partnerships are considered to be successful and whether and how they can contribute to aid effectiveness. While public-private partnerships have a great potential to be aid effective, great discipline is required to ensure they are established and implemented well. As such, a set of ten basic guidelines were developed to help policy makers and program designers in ensuring that their public-private partnerships are likely to contribute to aid effectiveness
Thesis (MPH)--University of the Philippines Manila, 2011
Keywords: Reproductive Health; Public-private sector cooperation